STUDY OF SORPTION PROPERTIES AND QUANTUM-CHEMICAL MODELING OF COMPOSITE MATERIALS IN RELATION TO URANIUM (VI) IONS - Satanova, Balzhan (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2025)
One of the most pressing issues in the field of environmental safety today is the protection of surface and groundwater from pollution of heavy metals and radionuclides, most of which can be found in industrial wastewater. That is, sorption technologies are widely used to remove pollutants. In most cases, these technologies provide access to scientifically based standards for the maximum permissible amount of pollutants in water. Natural and wastewater treatment technologies make it possible to widely use various layered raw materials, including clay minerals. The advantage of their use is due to the low cost of raw materials with sufficiently high sorption characteristics in relation to inorganic toxicants. So, in some cases, due to the insufficient selectivity of such sorbents, it is necessary to remove traces of pollutants, especially from waters of complex chemical composition, which contain complex-forming components of natural and man-made origin. Synthetic inorganic silicon-based sorbents are obtained by various methods of surface functionalization of sorbents to increase selectivity. Such methods include the use of organosilicon compounds containing active acid groups (SH, COOH, P(O)(OH)2), basic groups (primary,secondary and tertiary amino groups, pyridine) and their combinations.